Functional Capacity and Levels of Physical Activity in Aging: A 3-Year Follow-up - Tomás, Maria Teresa; Galán-Mercant, Alejandro; Carnero, Elvis Alvarez; Fernandes, Beatriz (Frontiers in Medicine, 2018)
Over the last decades, the world elderly population has increased exponentially and this tendency will continue during the coming years; from 2000 to 2050 people over 60 will double and those over 80 will quadruple. Loss of independence occurs as people age due to mobility restrictions, frailty and decreased functional fitness and cognitive abilities. Evidence has shown that appropriate programs and policies contribute to keep older adults healthy and independent over time. The purpose of this chapter is to report the results of our 3-years follow-up study designed to characterize functional physical fitness in a sample of Portuguese community-dwelling older adults to propose a set of functional parameters which decline the most. We studied a group of 43 elderlies, aged 60 and over. Variables assessed on the participants, were anthropometrics characteristics, functional capacity with the Senior Fitness Test battery (muscle strength, aerobic endurance, flexibility, agility and dynamic balance), handgrip strength, levels of physical activity and balance. Three years after the first assessment a second assessment of the same variables was conducted. We have analyzed what were the variables that, for this group, were related with a better ageing and the relation with different physical activity levels. Our study showed that the distance walked in 6MWT and handgrip strength seem to explain a great amount of variability on functional variables that have changed on this period (68% of balance, 57% and 48% of strength lower strength vs upper strength) and the active participants showed less decrements with ageing in anthropometric and functional variables than those inactive or insufficiently active (p<0,05). Greater importance should be given to prescription of exercise targeting older adults and specifically, walking and manual activities should be given more attention as components of a community exercise program.